MicroRNAs as Potential Regulators of Docosahexaenoic Acid Benefits in Alzheimer#x2019;s Disease (Global Journal of Medical Research, 2021)
Alzheimer#x2019;s disease (AD) is a highly prevalent neurodegenerative disease that imposes a prodigious burden on the society. Docosahexaenoic acids (DHA) are known to be beneficial in AD, in part through their anti-inflammatory properties. MicroRNAs (miRs) are important regulators of brain functions and this regulation becomes disrupted in AD. Objectives: The purpose of this article is to propose the involvement of miRs in the antiinflammatory effects of DHA on AD. Methods: The literature surrounding this topic is extensively researched: miR involvement in the pathophysiology of AD, the mechanism of action of DHA, the effects of DHA on miRs and potential future therapeutic strategies for AD involving miRs. Results: AD results in a disrupted miR network that relates to inflammation, but the altered miRs vary between studies. The effects of DHA on AD are generally positive but the mechanism remains enigmatic. Emerging studies demonstrate that one of the potential mechanisms of action of DHA is modulation of miRs.
Keywords: Omega-3; Diet; Anti-inflammatory; Inflammation; Nutrigenetics; Food-derived microRNA; Exogenous microRNA